The Effect of Clinical Supervision on Nurse Performance - Rahayu Tri Nuritasari; Erfan Rofiqi; Tan Nina Fibriola; Rizal Tri Ardiansyah (Jurnal Ners, 2019)
The nursing department often incurs problems about the performance of the nurses in providing nursing care at the hospital. This condition must get the attention of the head of the room as the manager who is directly responsible for the nursing care provided by the implementing nurse. Supervision is a part of the directional function that has the role of maintaining the department so then all programmed activities can be carried out properly and smoothly. This systematic review was conducted to review the effect of clinical supervision on nurse performance. For the systematic review, a literature search of the PubMed, SAGE, Science direct, and Scopus databases using the keywords ‘nursing’, ‘clinical supervision’, ‘clinical performance’ and ‘nurse performance’ was conducted in February 2019. The search identified 15 relevant research articles from the 2.436 original articles and full texts published between 2013 and 2019. The results show that clinical supervision has the potential to improve staff performance, which will ultimately affect the successful attainment of the hospital. Support from the hospital nursing management in providing support and monitoring is critical to the continuity, sustainability and successful implementation of clinical supervision. Clinical supervision activities conducted regularly in a scheduled manner will spur on the nurse’s performance.